EVALUATION OF THE EFFICIENCY OF COMBINED MINING METHODS IN COMPLEX UNDERGROUND DEPOSITS - Solixov J. X.; Shomurodov Sh. M.; Juraboyeva D. H. (Web of Journals Publishing, 2025)
Underground mining operations in geologically complex deposits require innovative and efficient extraction methods. This study evaluates the effectiveness of combined mining systems in such environments, focusing on productivity, cost, safety, and environmental impact. A comparative analysis is conducted using data from selected caase studies and simulation models.
Keywords: Combined mining methods, complex underground deposits, ore recovery, dilution, mining efficiency, sublevel caving, cut and fill, hybrid mining systems, mining safety, energy consumption in mining, geomechanical conditions, operational cost, underground mining technologies, mining productivity, environmental impact of mining.